2022
DOI: 10.1038/s41419-022-04767-z
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor REV-ERBα is implicated in the alteration of β-cell autophagy and survival under diabetogenic conditions

Abstract: Pancreatic β-cell failure in type 2 diabetes mellitus (T2DM) is associated with impaired regulation of autophagy which controls β-cell development, function, and survival through clearance of misfolded proteins and damaged organelles. However, the mechanisms responsible for defective autophagy in T2DM β-cells remain unknown. Since recent studies identified circadian clock transcriptional repressor REV-ERBα as a novel regulator of autophagy in cancer, in this study we set out to test whether REV-ERBα-mediated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…REV-ERBα mRNA and protein expressions were cytokine-coregulated and both potentiated by synchronization. Pharmacological activation of REV-ERBα impairs autophagy and insulin expression and secretion while promoting apoptosis in β-cells, likely through clock-independent transcriptional effects [24, 47]. The loss of β-cell function and increased apoptosis might be an effect of impaired autophagy, as loss of autophagy results in loss of β-cell mass in mice [48].…”
Section: Discussionmentioning
confidence: 99%
“…REV-ERBα mRNA and protein expressions were cytokine-coregulated and both potentiated by synchronization. Pharmacological activation of REV-ERBα impairs autophagy and insulin expression and secretion while promoting apoptosis in β-cells, likely through clock-independent transcriptional effects [24, 47]. The loss of β-cell function and increased apoptosis might be an effect of impaired autophagy, as loss of autophagy results in loss of β-cell mass in mice [48].…”
Section: Discussionmentioning
confidence: 99%
“…BartoloméA et al (47) demonstrated that chronic overactivation of mTORC1 in a mouse model (b-tsc2 -/-) led to increased pancreatic b-cell death and impaired autophagy. In a separate study, Matthew R. Brown et al (48) found that negative regulation of REV-ERBa may improve b-cell function under glucotoxicity by enhancing autophagy. This was achieved by investigating the link between the core circadian clock nuclear receptor REV-ERBa, autophagy, and b-cell failure.…”
Section: Autophagy and B Islet Cellsmentioning
confidence: 99%
“…In a separate study, Matthew R. Brown et al. ( 48 ) found that negative regulation of REV-ERBα may improve β-cell function under glucotoxicity by enhancing autophagy. This was achieved by investigating the link between the core circadian clock nuclear receptor REV-ERBα, autophagy, and β-cell failure.…”
Section: Correlation Between Autophagy and T2dm As Well As Its Compli...mentioning
confidence: 99%
“…Therefore, inhibiting excessive apoptosis in pancreatic β cells is crucial for the treatment of DM. Studies have confirmed that impaired autophagy regulation is associated with pancreatic β-cell failure in type 2 diabetes (T2DM) ( 15 ). However, the mechanism of autophagy in type 1 diabetes remains unclear.…”
Section: Autophagy Diabetes and Diabetic Complicationsmentioning
confidence: 99%